Illegally Parked Vehicles: A Policy and Practice Perspective - Suci Humaira, Mutia; Dianti, Tiara Sabrina; Wulandari, Sri (Devotion : Journal of Research and Community Service, 2024)
Parking problems greatly affect traffic flow, especially in crowded areas. Illegal parking occurs illegally or without an official permit from the local government, is not under the supervision or guidance of the district or city government, and the income from the parking is not paid to the government as regional revenue. Illegal parking in Cirebon City can be a problem because it does not comply with the applicable rules. The purpose of this study is to find out how parking arrangements are arranged from the perspective of policy and practice. This research method uses a qualitative method. Data collection techniques carried out by researchers with observations, interviews, documents and legislation that are related to the problem being researched. The results of the study show that the problem of illegal parking occurs due to the number of parking lots that use the road body, because the lane that should be used for vehicle flow is instead used for parking. In practice, sometimes the enforcement of these rules is inconsistent due to the limitations of direct supervision. Even though the parking attendants were warned not to allow double parking and had been given guidance, violations still occurred. The conclusion of this study is that the problem of illegal parking lies in individuals' awareness of traffic rules and their discipline in obeying them.